Pentraxin-3, Troponin T, N-Terminal Pro-B-Type Natriuretic Peptide in Septic Patients. Issue 5 (November 2020) - Vassalli, Francesco; Masson, Serge; Meessen, Jennifer; Pasticci, Iacopo; Bonifazi, Matteo; Vivona, Luigi; Caironi, Pietro; Busana, Mattia; Giosa, Lorenzo; Macrì, Matteo Maria; Romitti, Federica; Novelli, Deborah; et al.
ABSTRACT: Objective: To investigate the behavior of pentraxin-3 (PTX3), troponin T (hsTnT), N-terminal pro-B type Natriuretic Peptide (NT-proBNP) in sepsis and their relationships with sepsis severity and oxygen transport/utilization impairment. Design: Retrospective analysis of PTX3, hsTnT, NT-proBNP levels at day 1, 2, and 7 after admission in the intensive care unit in a subset of the Albumin Italian Outcome Sepsis database. Setting: Forty Italian intensive care units. Patients: Nine hundred fifty-eight septic patients enrolled in the randomized clinical trial comparing albumin replacement plus crystalloids and crystalloids alone. Interventions: The patients were divided into sextiles of lactate (marker of severity), ScvO2 (marker of oxygen transport), and fluid balance (marker of therapeutic strategy). Measurements and Main Results: PTX3 and hsTnT were remarkably similar in the two treatment arms, while NT-proBNP was almost double in the albumin treatment group. However, as the distribution of all these biomarkers was similar between control and treatment arms, for the sake of clarity, we analyzed the patients as a single cohort. PTX3 (71.8 [32.9–186.3] ng/mL), hsTnT (50.4 [21.6–133.6] ng/L), and NT-proBNP (4, 393 [1, 313–13, 837] ng/L) were abnormally elevated in 100%, 84.5%, 93.4% of the 953 patients and all decreased from day 1 to day 7. PTX3 monotonically increased with increasing lactate levels. The hsTnT levels were significantly higher when ScvO2 levels were abnormally low (< 70%), suggesting impaired oxygen transport compared with higher ScvO2 levels, suggesting impaired oxygen utilization. NT-proBNP was higher with higher lactate and fluid balance. At ScvO2 levels < 70%, the NT-proBNP was higher than at higher ScvO2 levels. However, even with higher ScvO2, the NT-proBNP was remarkably elevated, suggesting volume expansion. Increased level of NT-proBNP showed the strongest association with 90-day mortality. Conclusions: The selected biomarkers seem related to different mechanisms during sepsis: PTX3 to sepsis severity, hsTnT to impaired oxygen transport, NT-proBNP to sepsis severity, oxygen transport, and aggressive fluid strategy. Abstract : Supplemental Digital Content is available in the text